Importance of electronic correlations and unusual excitonic effects in formamidinium lead halide perovskites - Whitcher, T. J. (2018)
Hybrid inorganic-organic perovskites have recently attracted much interest because of both rich fundamental sciences and potential applications such as the primary energy-harvesting material in solar cells. However, an understanding of electronic and optical properties, particularly the complex dielectric function, of these materials is still lacking. Here, we report on the electronic and optical properties of selective perovskites using temperature-dependent spectroscopic ellipsometry, x-ray absorption spectroscopy supported by first-principles calculations. Surprisingly, the perovskite FA0.85Cs0.15PbI2.9Br0.1 has a very high density of low-energy excitons that increases with increasing temperature even at room temperature, which is not seen in any other material. This is found to be due to the strong, unscreened electron-electron and partially screened electron-hole interactions, which then tightly connect low- and high-energy bands caused by doping.